Attachment representations and autonomic regulation in maltreating and nonmaltreating mothers. (20th October 2016) - Reijman, Sophie; Alink, Lenneke R. A.; Compier-De Block, Laura H. C. G.; Werner, Claudia D.; Maras, Athanasios; Rijnberk, Corine; Van Ijzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.
Abstract: This study assessed attachment representation and attachment-related autonomic regulation in a sample of 38 maltreating and 35 nonmaltreating mothers. Mothers' state of mind regarding attachment was measured using the Adult Attachment Interview. They further watched an attachment-based comfort paradigm, during which we measured skin conductance and vagal tone. More maltreating mothers (42%) than nonmaltreating mothers (17%) had an unresolved/disoriented attachment classification. Attachment representation was related to physiology during the comfort paradigm: an unresolved state of mind and a nonautonomous classification were associated with a decrease in skin conductance during the comfort paradigm, specifically during the responsive caregiver scenario. However, physiology did not differ between maltreating and nonmaltreating mothers. The decrease in skin conductance of unresolved mothers during the comfort paradigm might be indicative of a deactivating response, which is congruent with the dissociative nature of the unresolved state of mind. The results point to the potential utility of interventions focused on attachment representations for maltreating mothers.